1980
DOI: 10.1111/j.1533-8525.1980.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Alienation as a Social Process

Abstract: This essay examines the concept of alienation with reference to Marxian and social psychological perspectives. A synthesis of these diverse perspectives is established with particular emphasis on work alienation. Noting that alienation is a consequence of situationally specific relations based on the interaction of historical context, structural conditions, and individual participants, a theoretical model is constructed for a view of alionation as a social process. It is suggested that understanding alienation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…These resonated with the data, based on the students' self-reported perceptions of their school conditions, and belief in their power to change those conditions (powerlessness); relationships with teachers and peers, and extracurricular involvement (social isolation); and records of achievement and (Miles & Huberman, 1994;Patton, 2002). I found that groups of students shared beliefs and behaviors that could be designated as low, medium, and high levels of alienation from school (Twining, 1980; see Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These resonated with the data, based on the students' self-reported perceptions of their school conditions, and belief in their power to change those conditions (powerlessness); relationships with teachers and peers, and extracurricular involvement (social isolation); and records of achievement and (Miles & Huberman, 1994;Patton, 2002). I found that groups of students shared beliefs and behaviors that could be designated as low, medium, and high levels of alienation from school (Twining, 1980; see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…When individuals perceive social arrangements as demeaning or unfair, they begin to recoil from major spheres of social life (Twining, 1980, p. 422). Their sense of separation from the social environment, or alienation, manifests as powerlessness, isolation, and normlessness (Newmann, 1981;Seeman, 1959Seeman, , 1975Seeman, , 1983Stanton-Salazar, 2001;Twining, 1980).…”
Section: Tainesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeman, 1975). However, most scholars have concluded that the core of alienation is uni-dimensional, rather than multi-dimensional, and lends itself to notions of self-estrangement (Kanungo, 1982;Mottaz, 1981;Twining, 1980). Vohra (2009), like Schacht (1970) and Mottaz (1981), argued that the heart of alienation is estrangement, or a disconnection between a person and his or her work.…”
Section: Alienationmentioning
confidence: 99%
“…By alienation, I refer to a thorough lack of control that people may come to have over their socioeconomic situation and by extension even over the very barest circumstances of existence itself. Alienation, in this regard, is a social process (Twining 1980), located at the intersection between "social-structural conditions and psychological orientation" (Kohn 1976: 111). For the retirees, alienation becomes the primary mode of experiencing life in the context of deferred gratuity.…”
mentioning
confidence: 99%